2011
DOI: 10.1177/1557988311414045
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Symptom Profiles Among Female and Male Victims of Sexual Violence

Abstract: Sexual violence is a serious public health problem that has been associated with negative mental and physical health outcomes. Few existing studies have examined the prevalence and patterns of adverse mental health among victims of sexual violence using data from nationally representative samples of U.S. adults. The main objectives of this study were to identify patterns in the associations between sexual violence victimization and depression and anxiety (DA) symptoms using data from the sexual violence and DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
2
38
0
6
Order By: Relevance
“…Experiencing gender-based violence can have tremendous consequences for the survivor’s mental and physical functioning, increasing the risks of poor health in general and of certain conditions, such as depression, Post-Traumatic Stress Disorder, anxiety, and chronic pain in particular [1,2,3]. Research has consistently demonstrated that sexual violence victimizations are in fact not an exception, but do affect a considerable proportion of women in any given population [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing gender-based violence can have tremendous consequences for the survivor’s mental and physical functioning, increasing the risks of poor health in general and of certain conditions, such as depression, Post-Traumatic Stress Disorder, anxiety, and chronic pain in particular [1,2,3]. Research has consistently demonstrated that sexual violence victimizations are in fact not an exception, but do affect a considerable proportion of women in any given population [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, sexual violence victimizations can happen to everybody [2,4,5,22]—although women are definitely at a higher risk of experiencing sexual violence in their lives as compared to men [6,23]. However, previous research has identified certain individual and contextual factors associated with an increased risk of becoming a survivor of sexual violence.…”
Section: Introductionmentioning
confidence: 99%
“…It is a major problem worldwide (WHO, 2013), associated with a wide range of negative effects on survivors' wellbeing (Martin et al, 2011; Choudhary et al, 2012). Studies demonstrating the high prevalence of sexual aggression as reported by victims and perpetrators have been conducted primarily in Western countries (Fisher et al, 2010; KrahĂ© et al, 2014, for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Another well-known fact is the association between ex-perience of violence and mental ill health [11][12][13][14][15]. Mental ill health is an overarching definition including mental disorders and milder psychological problems or distresses which generate personal suffering but not necessarily a psychiatric diagnosis [16].…”
Section: Introductionmentioning
confidence: 99%